Vitaminstatus bei geriatrischen Patienten: Zusammenhang mit Körperstatus und kognitiven Funktionen - Hannah Marie Werner (Hochschule für angewandte Wissenschaften Hamburg, 2019)
In addition to changes in cognitive and physical functions, there is a higher risk of vitamin deficiency in older people. Due to the demographic change, it is necessary to analyze the connections between geriatric multimorbidity occurring in old age. Vitamin D, vitamin B12 and folate are the most critical nutrients. The study objective is to investigate the relationship between vitamin status and body sta-tus as well as between vitamin status and cognitive function. This retrospective cross-sectional study involved 607 patients hospitalized in a geriatric ward in Germany from January to July 2019 (mean age: 82,35 ± 6,91 years). 51.5 % of the patients are at risk for malnutrition. The body status was measured using body-mass-index (BMI) and handgrip strength. The level of cognitive function was measured by Mini Mental State Examination (MMSE). The serum 25-hydroxy vitamin D, total vitamin b12 in serum and serum folate were measured with Chemiluminescence Immunoassay (CLIA). The Independent Samples t-Test was used to identify a difference between patients with vitamin deficiency and patients with normal vitamin status in terms of BMI, handgrip strength and MMSE. The mean BMI is 26,73 ± 6,49 kg/m², mean handgrip strength is 39,69 ± 17,13 kPa and mean value of MMSE is 22,43 ± 6,38. In total, 73,1 % of the patients have a vitamin D deficiency (<30 μg/l), 11,0 % a vitamin b12 deficiency (<180 pg/ml) and 5,9 % a folate deficiency (<3,0 ng/ml). This study supports the relationship between vitamin status and body status in hospitalized geriatric patients. Among ≥80-year-olds, a significant correlation can be found between vi-tamin D and BMI (p=0.040) and between folate and BMI (p=0.033). A tendency is observed for the relationship between vitamin D and BMI in women (p=0.064). No significant associ-ation can be found between vitamin status and cognitive function. Due to the heterogeneity of the sample, further studies are required.